Regulatory Fragmentation: An Unexamined Barrier to Species Conservation Under Climate Change - Camacho, Alejandro E.; McLachlan, Jason S. (Frontiers in Climate, 2021)
Requirements for the protection or restriction of species are based on regulatory classifications such as "native" or invasive," which become anachronistic when climate change drives species outside of their historical geographic range. Furthermore, such regulatory classifications are inconsistent across the patchwork of land ownership that species must traverse as they move between jurisdictions or when transported by humans, which obstructs effective regional management. We surveyed the laws and regulations relevant to species movement and found that the immigration of species to new jurisdictions makes paradoxical existing regulatory language that sets the categories of species deserving protection or removal. Climate change is universal and progressing rapidly, which provides a shrinking window to reconcile regulatory language originally developed for a static environment.